Activation of the BMP-BMPR pathway conferred resistance to EGFR-TKIs in lung squamous cell carcinoma patients with EGFR mutations - Wang, Zhijie (Proc Natl Acad Sci U S A, 2015)
The empirical criteria for defining a clinical subtype of lung cancer are gradually transiting from histopathology to genetic variations in driver genes. Targeting these driver mutations, such as sensitizing epidermal growth factor receptor (EGFR) mutations, has dramatically improved the prognosis of advanced non–small cell lung cancer (NSCLC). However, the clinical benefit of molecularly targeted therapy on NSCLC appears to be different between lung adenocarcinomas and squamous cell carcinomas (SqCCs). We report here that the resistance of lung SqCC harboring EGFR mutations to EGFR tyrosine kinase inhibitors (EGFR-TKIs) was due to the activation of BMP-BMPR-Smad1/5-p70S6K. The combined treatment of these tumor cells with EGFR-TKI, together with inhibitors specific to BMPR or downstream mTOR, effectively reversed the resistance to EGFR-TKI. Moreover, blocking the whole PI3K-AKT-mTOR pathway with the PI3K/mTOR dual inhibitor BEZ235 also showed efficacy in treating this subtype of lung SqCC. This study details the empirical basis for a feasible clinical solution for squamous cell carcinomas with EGFR mutations.